Penguatan Kelembagaan Kelompok Tani melalui Integrasi Kemandirian Wirausaha dan Pengelolaan Irigasi Berkelanjutan - Yozi Putri Sakinah; Furqani, Fahma; Depi, Juwita Wirta Sri; Putra, M. Farrasky Delas; Husna, Ainal; Fachri, Ahmad (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This community service activity aims to strengthen the institutional capacity of the Muaro Saiyo Farmers Group through the integration of entrepreneurial independence and sustainable irrigation management. The main issues faced by the group are the weakness of the organizational structure, low entrepreneurial skills, and poorly coordinated irrigation management. The implementation methods include field surveys, socialization, thematic training (institutional management, post-harvest processing, and sustainable irrigation), mentoring, and evaluation through pre-tests and post-tests to measure changes in knowledge. The results of the activity show a significant increase in participants' knowledge, which improved from 25.9% in the